Credit constraints in education - Lance Lochner; Alexander Monge-Naranjo (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2012)
We review studies of the impact of credit constraints on the accumulation of human capital. Evidence suggests that credit constraints have recently become important for schooling and other aspects of households' behavior. We highlight the importance of early childhood investments, since their response largely determines the impact of credit constraints on the overall lifetime acquisition of human capital. We also review the intergenerational literature and examine the macroeconomic impacts of credit constraints on social mobility and the income distribution. A common limitation across all areas of the human capital literature is the imposition of ad hoc constraints on credit. We propose a more careful treatment of the structure of government student loan programs and the incentive problems underlying private credit. We show that endogenizing constraints on credit for human capital helps explain observed borrowing, schooling, and default patterns and offers new insights about the design of government policy.
Keywords: D14; H52; I22; I23; J24; 330; Human Capital; Incentive Problems; Government Loans; Early Investments; Social Mobility